Commentary on the Old Testament ; v. 10 - Keil, Johan Karl Friedrich, 1807-1888; Delitzsch, Franz Julius, 1813-1890; Martin, James (Grand Rapids, MI Eerdmans)
Contents : v. 10 : Minor Prophets / C.F. Keil. Includes bibliographical references.
Reprinted 1973.
Keywords: Bible. O.T. -- commentaries